Use of the graphic calculator in teaching mathematics as a means to increase the level of practical thinking of students of higher education institutions - V V Bogun (RUDN Journal of Informatization in Education, 2013)
The role of the graphic calculator to increase the level of practical thinking of students of higher education institutions when training mathematics is discussed in the article.